Prolonged running increases knee moments in sidestepping and cutting manoeuvres in sport. Issue 5 (May 2018) - Savage, Robert J.; Lay, Brendan S.; Wills, Jodie A.; Lloyd, David G.; Doyle, Tim L.A.
Abstract: Objectives: To investigate how knee kinematics, kinetics and loading changes during sidestepping tasks following a prolonged running protocol performed in a laboratory setting. Design: All participants performed sidestepping, and crossover cutting tasks in a randomised order before and after a 60 min running protocol on a non-motorised treadmill that simulated an AF game. Methods: Eight healthy male participants who partook in semi-professional and amateur Australian Football undertook a series of straight line runs, sidestepping (SS), and crossover cutting (XO) tasks before and after a simulated game of Australian football. Kinematic data were analysed at initial foot contact of the SS and XO manoeuvres and kinetic data were analysed during the weight acceptance phase of the stance. Results: The knee was significantly more flexed at foot contact following fatigue compared to pre-fatigue states. Fatigue was also a factor contributing to significant increases in internal knee extension moments. Significant differences were also observed between SS and XO trials with flexion/extension moments, with notable differences in varus/valgus and internal/external rotation moments. Conclusions: Acute angles of knee flexion at foot strike in a fatigued state may place the joint at an increased risk of injury. Increases in knee extension moments in the fatigued state suggests the knee joint must withstand significantly high stresses once fatigued.